Management of Grahani Roga (Acute Pancreatitis) by Ayurvedic Modalities: A Case Report - Sonali Balu Sahane; Renu Bharat Rathi; Pavan Navkarkar; Shrish Jaishwal (Journal of Clinical and Diagnostic Research)
Acute pancreatitis is one of the most critical health conditions in the paediatric age group. A one-to-one correlation of pancreatitis is not found in Ayurveda classics; however, it can be considered under Grahani Roga. Hereby, the authors present a case report of a five-year-old male patient complaining of recurring pain in the epigastric and left hypochondriac regions, referred to the back, along with nausea and severe projectile vomiting. The patient was diagnosed just five days ago with Grahani Roga (acute pancreatitis) using ultrasonography and laboratory findings, and he approached the Kaumarbhritya (Paediatric) Outpatient Department (OPD) for management. Considering the severity of the disease and the condition of the patient, Ayurvedic Shamana and Shodhana Chikitsa were initiated. Grahani Roga (acute pancreatitis) is classified as a Pittaj Vikara. Virechana is the best treatment modality for Pittaj Vikara; hence, in this patient, Mridu Virechana (mild purgation) using Avipattikar Churna was administered. Due to the extreme pain in the patient, which is associated with Vata Dosha vitiation, Matra Basti with Til Taila was started. Alongside this, Shamana Aushadhi was initiated, which included Sankh Vati, Aamlaki Churna, and Yashtimadhu Churna as Rasayana drugs. After eight days of treatment, improvement was observed in symptoms such as abdominal pain and nausea. Shamana and Shodhana Chikitsa were continued for 21 days, resulting in significant improvement in overall symptoms. No recurrence had been observed until the sixth month of follow-up.